Efficacy of Thumari (Securinega leucopyrus) Ointment and Betadine Ointment in Managing Shastrakruta Vrana: A Randomised Controlled Trial Research Protocol - Devesh Hetram Nagpure; Sheetal Gajanan Asutkar (Journal of Clinical and Diagnostic Research)
Introduction: Acharya Sushruta highlighted the enduring significance of wounds in surgery, addressing various types caused by trauma and imbalances in Vata, Pitta, and Kapha (the fundamental energies governing physiological and psychological functions). Thumari, or Katupila (Securinega leucopyrus), a traditional remedy from India and Sri Lanka, is renowned for its exceptional wound-healing properties, including purification, healing, and skin restoration. Need of the study: Surgical site infections are a significant concern in India (23-38% incidence), and Betadine ointment’s potential side effects (skin irritation, redness, itching) underscore the need for improved wound healing options. Thumari-based products (gel, oil, kalka) have demonstrated effective wound healing, anti-inflammatory, analgesic, antibacterial, and antifungal properties, attributed to their tannin and flavonoid content. While small-scale studies show positive results, larger comparative trials are needed to confirm Thumari’s efficacy. Aim: To evaluate the comparative efficacy of Thumari ointment and Betadine ointment in managing Shastrakruta Vrana (surgical wounds). Materials and Methods: This randomised controlled trial (CTRI/2023/02/049990) will be conducted at Mahatma Gandhi Ayurveda College Hospital and Research Centre (MGACHRC), Salod Hirapur, Maharashtra, India (March 2023-October 2024). Seventy patients (aged 18-60 years) will receive either Betadine or Thumari ointment for local application on their surgical wounds. Assessment parameters include pain, tenderness, colour, margin, discharge, inflammation, and healing time. Data analysis will use Mann-Whitney U test, Chi-square test, and Independent t-test (SPSS 27.0; p<0.05 for significance).